Analisis Sistem Informasi Akuntansi Penerimaan Dan Pengeluaran Kas Pada PT. Anjungan Buana Wisata - Laura Parasti; Ayu Feranika (Journal of Applied Accounting And Business, 2021)
PT. The Jambi Tourism Buanan Pavilion is a company in the tourism sector with the trademark Kampoeng Radja. The problem is that Kampoeng Radja is the only largest tourist park in Jambi Province that uses technological developments in the form of cards (Kampoeng Radja Cards) in the ticket system, because it is still the only tourist park that uses ticket system technology, so this study aims to analyze the information system process. accounting for cash receipts and disbursements at the ongoing PT Anjungan Buana Wisata. This research uses descriptive analysis method. Data collection techniques, using the method of interviewing, observation, and literature study. The results showed that; (1) The accounting system for cash receipts and disbursements at PT. The Buana Wisata Pavilion is carried out systematically, all processes of cash receipts and cash disbursements must be authorized by the parties concerned. (2) There is a separation of the functions of finance, accounting and cash so that security can be guaranteed. This is in accordance with the theory and is well implemented at PT. Buana Wisata Pavilion. (3) Cash receipt and receipt system supported by an excellent internal control system. (4) The company has used a computer system to record all transactions. All data has been automatically available in this system which is very effective and efficient for the company.